Nonstructural protein 3 of hepatitis C virus blocks the distribution of the free catalytic subunit of cyclic AMP-dependent protein kinase. - Borowski, P (1997)
Chronic hepatitis resulting from hepatitis C virus (HCV) infection develops into cirrhosis in at least half of infected patients and increases the risk of hepatocellular carcinoma. The pathogenic effects of a number of viruses result from the disturbance of intracellular signal cascades caused by viral antigens. Therefore, we investigated the interaction of nonstructural protein 3 (NS3) of HCV with the cyclic AMP-dependent signal pathway. We found a similarity between the HCV sequence Arg-Arg-Gly-Arg-Thr-Gly-Arg-Gly-Arg-Arg-Gly-Ile-Tyr-Arg localized in NS3 and the general consensus sequence of protein kinase A (PKA). Consequently, the catalytic (C) subunit of PKA bound to a bacterially expressed fragment of HCV polyprotein containing amino acid residues 1189 to 1525. When this fragment was introduced into cells, it inhibited the translocation of the C subunit into the nucleus after stimulation with forskolin. The result of this inhibition was significantly reduced histone phosphorylation. Therefore, the presence of NS3 in the cytoplasm of infected cells may affect a wide range of PKA functions and contribute to the pathogenesis of the diseases caused by HCV.